Quo Vadis Penyiaran Over-The-Top: Meluruskan Kedaulatan Kelembagaan Pengawas Penyelenggara Sistem Elektronik - Alif Duta Hardenta; Zuhdi Fansuri Ariawan; Akhmad Farhan Nazhari (Fakultas Hukum Universitas Udayana, 2022)
Over-The-Top (OTT) media-based Electronic System Operators are increasingly being used by the public as a result of media convergences and internet services. Nevertheless, the use of OTT services raises various problems, ranging from problems of threats to users, to regulatory issues for OTT. So far, OTT services are not regulated in a standard manner in one comprehensive law, causing uncertainty for both the consumer and its competitors, which are arranged by some regulatory attestation. This problem then became tangible when one of the broadcast services tried to appeal related to the definition and scope of regulation from the OTT services to the Constitutional Court. Based on these complications, it can be stated that there is a need for legal arrangements followed by institutions from the OTT supervisor. Therefore, the researcher elaborates the status quo with the problems of implementing the OTT services. With the description of the problem, together with further comparisons between countries, the researcher can conclude the arrangements for OTT organizers that can be included in legal regulations. In this study, several policy strategies were formulated for the implementation of institutional arrangements in the OTT services.